2017
DOI: 10.1002/ajcp.12116
|View full text |Cite
|
Sign up to set email alerts
|

Do Community Characteristics Relate to Young Adult College Students’ Credit Card Debt? The Hypothesized Role of Collective Institutional Efficacy

Abstract: This study examines the extent of emergent, outstanding credit card debt among young adult college students and investigates whether any associations existed between this credit card debt and the characteristics of the communities in which these students grew up or lived. Using data (N = 748) from a longitudinal survey and merging community characteristics measured at the zip code level, we confirmed that a community's unemployment rate, average total debt, average credit score, and number of bank branch offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…In a follow-up study, Norvilitis et al (2006) found that the lack of financial knowledge, age, delay of gratification, number of credit cards, and attitudes toward credit card use were related to debt. Individual characteristics (e.g., race and financial independence) and familial characteristics (e.g., their parents' income and parents' discussions of financial matters while growing up at home) were associated with a young adult college student's acquisition and accumulation of credit card debt (Friedline et al, 2017). In a more recent study, Limbu (2017) found that knowledge about credit card and social motivation were inversely associated with credit card misuse mediated through credit card self-efficacy.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a follow-up study, Norvilitis et al (2006) found that the lack of financial knowledge, age, delay of gratification, number of credit cards, and attitudes toward credit card use were related to debt. Individual characteristics (e.g., race and financial independence) and familial characteristics (e.g., their parents' income and parents' discussions of financial matters while growing up at home) were associated with a young adult college student's acquisition and accumulation of credit card debt (Friedline et al, 2017). In a more recent study, Limbu (2017) found that knowledge about credit card and social motivation were inversely associated with credit card misuse mediated through credit card self-efficacy.…”
Section: Introductionmentioning
confidence: 95%
“…Some studies have explored the factors that influence university students' credit card debt (e.g., Friedline, West, Rosell, Serido, & Shim, 2017;LaRose & Eastin, 2002;Limbu, 2017;Serido et al, 2015;J. Wang & Xiao, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in the local financial services environment matter because of the relationships between neighborhoods' brick-and-mortar financial services and their residents' participation in economic life, such as paying bills (Friedline, Despard, and West 2017a), receiving health care (Eisenberg-Guyot et al 2018;Melzer 2011), and accessing credit (Bertrand and Morse 2011;Bhutta 2014;Bhutta, Skiba, and Tobacman 2015;Friedline et al 2017b). For instance, having banks within closer proximity to or more highly concentrated in neighborhoods is associated with being more likely to use these financial services, have access to credit, and experience increased opportunities for entrepreneurship (Brown, Cookson, and Heimer 2016;Friedline et al 2017b;Kerr and Nanda 2009). The lack of bank access negatively impacts local small business lending, which leads to a reduction in employment growth rates, and these effects are particularly found to affect those living in lower-income neighborhoods (Nguyen 2014).…”
Section: The Local Financial Services Environmentmentioning
confidence: 99%
“…Emerging adults today face unique circumstances compared to previous cohorts, given the societal, cultural, and economic changes that have arisen in recent decades (Arnett, 2007). For instance, emerging adults have greater participation in postsecondary education and technical training, enter marriage and parenthood later in their lives, and have greater financial debt than previous generations (Arnett, 2007; Friedline et al, 2017). Moreover, emerging adults are living during a time with greater globalization (Gattino, Tartaglia, Rollero, & De Piccoli, 2019) and economic inequality (Herring & Henderson, 2016; Horowitz, Igielnik, & Kochha, 2020).…”
Section: Introductionmentioning
confidence: 99%